Design of miniaturized monopole antennas fed by gap source - Alireza Akbarzadeh (2009)
Antenna miniaturization is one of the most challenging tasks that antenna designers are encountering nowadays. Having a versatile electrically small antenna with a satisfactory radiation efficiency along with other components in a transceiver circuit has engendered a necessity for antenna designers to deal with this task prominently. Antenna parameters (e.g. radiated power, frequency bandwidth and radiation efficiency) are dependant upon its physical dimensions. Reducing the physical size of an antenna degrades its performance in a great deal. Fundamental limits have been determined as upper bounds on the performance of an electrically small antenna and it has been proved that one can slightly approach these limits in an ideal case. All the proposed methods to overcome the prevailing challenges in antenna miniaturization are divided into two general ways: 1) using novel structures, 2) loading the antenna with materials. The idea behind the first method is to increase the effective volume of the antenna while its physical volume is unchanged. Increasing the effective volume of the antenna, its current distribution would be improved and the near field storage would be reduced. In the second method, it is aimed to load the antenna with dielectric materials to reduce its resonance frequencies.